Promosi yang Dilakukan Dhinda Hijab Dalam Menjaga Loyalitas Pelanggan - Arni Eza Putri; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty; Hanapiah Halimatu Sya’diah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of carrying out this industrial visit is to find out about the promotion of dhinda hijab in maintaining customer loyalty. The method used in this study is descriptive with observation, data collection using interview techniques, observation, documentation, and literature. dhinda hijab has increased and is starting to be known by many people as a hijab brand with quality that is comfortable to wear, to maintain customer satisfaction Dhinda Hijab makes it easy for its customers, namely by spreading information on various internet media so that they can easily access the products they are looking for or want through social media like Instagram, Shopee and Tiktok. The best social media for marketing and promoting is Tiktok, because there are many attractive promos such as discounted prices and free shipping which are easy to get, and if calculated from administrative costs for sellers, Tiktok is lower than other social media. Digital marketing makes it easier for consumers to make purchases and provide product ratings, which can then be used as a benchmark for customer satisfaction and product evaluation for sellers.